Validitas dan Praktikalitas E-Modul Berbasis Mobile Learning Berbantuan 3D Page Flip Professional Pada Materi Ekologi dan Perubahan Lingkungan di Kelas X SMA - Abdul Razak; Lufri Lufri; Irdawati Irdawati; Muhamad Sholichin (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to produce a valid and practical Mobile Learning (ML)-Based E-Module Assisted by the 3D Page Flip Professional Application. This type of research is development research using the Plomp model. The development stage of this model begins with the initial investigation stage, the development or prototyping stage, and the assessment stage. The instruments used in this development research were teacher interview guideline instrument sheets, student response questionnaire sheets, self-evaluation sheets, and E-Module validation sheets by experts, as well as e-module practicality assessment sheets filled in by teachers and students. The results showed that the 3D Page Flip Professional Application Assisted Mobile Learning (ML) Based E-Module based on expert judgment was very valid with a score of 89.10%. Practicality assessment of student assessment in field trials (large group evaluation) with a score of 88.95% with very practical criteria, and practicality assessment by the teacher obtained a score of 93.75% with very practical criteria. It can be concluded that the 3D Page Flip Professional Application Assisted Mobile Learning (ML) Based E-Module that has been developed is in the category of very valid, and very practical.